2019
DOI: 10.1002/ana.25545
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 links inflammation to outcome after subarachnoid hemorrhage

Abstract: Objective: To investigate whether soluble growth stimulation expressed gene 2 (sST2), a prognostic marker in cardiovascular and inflammatory disorders, is associated with neurological injury after aneurysmal subarachnoid hemorrhage (SAH). Methods: We studied SAH patients from 2 independent cohorts. Outcome assessments included functional status at 90 days using the modified Rankin Scale (mRS), mortality, and delayed cerebral ischemia (DCI). The relationships between sST2 plasma level and outcome measures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Severe subarachnoid hemorrhage is associated with the strong early inflammatory response ( 88 ), and the most direct and easily observed result is the change in peripheral inflammatory biomarkers, such as the neutrophil and lymphocyte counts ( 89 , 90 ). In general, an increase in neutrophils in peripheral blood is a manifestation of inflammation in the CNS and may be related to the development of extracerebral organ immune dysfunction.…”
Section: Practice Prospectsmentioning
confidence: 99%
“…Severe subarachnoid hemorrhage is associated with the strong early inflammatory response ( 88 ), and the most direct and easily observed result is the change in peripheral inflammatory biomarkers, such as the neutrophil and lymphocyte counts ( 89 , 90 ). In general, an increase in neutrophils in peripheral blood is a manifestation of inflammation in the CNS and may be related to the development of extracerebral organ immune dysfunction.…”
Section: Practice Prospectsmentioning
confidence: 99%
“…Previous studies indicated that inflammatory response peaks at 24–48 h post-bleeding. And the elevated neuroinflammation is associated with higher clinical severity, delayed cerebral ischemia, mortality, and functional outcome after SAH ( Ahn et al, 2019 ; Bevers et al, 2019 ). In addition, recent studies suggested that inhibition of Enhancer of Zeste Homolog 2 (EZH2) or thromboxane-prostaglandin (TP) receptors could afford a robust neuroprotective effect against SAH via inhibiting neuroinflammation in a rat model of SAH ( Lagier et al, 2019 ; Luo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between hemorrhagic events and inflammatory responses has been well described in multiple cerebrovascular anomalies, including aneurysm ( 95 , 96 ), cerebral arteriovenous malformation ( 97 ), cerebral amyloid angiopathy ( 98 , 99 ), and ischemic cerebrovascular disorders ( 100 , 101 ). Notably, acute brain hemorrhages may not have an opportunity to lead a similar milieu with the longstanding deposition of blood products, because it would be absorbed over a normal length of time.…”
Section: Immune and Inflammatory Mechanisms For Complicationsmentioning
confidence: 99%